The Role Of Innovative Activities Of Highly Qualified Personnel In The Strategic Development Of The Regions - Abduqosim Abdulhakimovich Tojaliyev (International Scientific and Current Research Conferences, 2020)
The article discusses the development of innovative activities of highly qualified personnel in the strategic development of each region of the country.